Cost-Effective Processing of Carbon-Rich Materials in Ionic Liquids: An Expeditious Approach to Biofuels - Naz, S. (American Chemical Society, 2021)
This work presents a cost-effective approach for processing of renewable carbon-rich biomass using pyridinium-based Lewis acidic ionic liquids (LAILs). Rice husk as carbon-rich lignocellulosic waste was pretreated with a series of neutral and Lewis acidic ionic liquids to yield valuable intermediate platform monosaccharides. Novelty in the work lies in direct conversion of lignocellulosic carbohydrates into reducing sugars without their further conversion into 5-hydroxymethylfurfural or any other platform chemicals that are fermentation inhibitors for bioethanol production. The unconverted cellulose-rich material (CRM) is regenerated as a delignified material by the simultaneous addition of antisolvents. CRM and recovered lignin obtained after pretreatment were analyzed via scanning electron microscopy (SEM), thermogravimetric analysis (TGA), and Fourier transform infrared (FTIR) spectroscopy. The process was optimized with respect to a high yield of platform sugars and the quantity as well as quality of recovered CRM and lignin contents. Various reaction parameters involving the molecular structure of ionic liquids (ILs), Lewis acidic strength of ILs, biomass loading into IL, time, temperature, and biomass particle size were screened thoroughly. From all of the tested ILs, unsymmetrical 3-methylpyridinium IL having N-octyl substitution and chloroaluminate anion showed a greater conversion efficiency at 100 Â°C for 1.5 h. FTIR and SEM analyses of recovered CRM justify >90 lignin removal from rice husk. From all of the removed lignin, 60 wt of original lignin content was recovered. The Lewis acidic system possessed recycling ability up to 3 times for subsequent treatment of rice husk without a significant loss of efficiency. Â©